Fundamentals of Compressible Flow Mechanics - Bar-Meir, Genick (Open textbook library., 2021)
This book deals with an introduction to the flow of compressible substances (gases). The main difference between compressible flow and almost incompressible flow is not the fact that compressibility has to be considered. Rather, the difference is in two phenomena that do not exist in incompressible flow. The first phenomenon is the very sharp discontinuity (jump) in the flow in properties. The second phenomenon is the choking of the flow. Choking is when downstream variations don't effect the flow. Though choking occurs in certain pipe flows in astronomy, there also are situations of choking in general (external) flow.